eTwinning Projects – a Means to Promote Growth Mindset and Well-being in Education - MARIN, Diana-Crina; NEACȘU, Mihaela-Gabriela; BOCOȘ, Mușata-Dacia (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2026)
eTwinning projects provide an excellent opportunity to organize various didactic and educational activities based on international collaboration and cooperation. The learning opportunities offered to teachers and students participating in these projects are diverse and serve as a means to develop scientific, collaborative, pedagogical, language, and digital competencies. These projects are based on modern pedagogical approaches used in different educational environments, which promote well-being in the school environment and foster a growth mindset in education. We consider that eTwinning projects should be introduced to all future teachers during both their initial and continuous training. This paper outlines the benefits of collaboration between eTwinning ambassadors and university teachers and the benefits of participating in eTwinning projects.